Analisis Faktor-Faktor yang Memengaruhi Ekspor Komoditas Perikanan: Pendekatan Gravity Model - Indrajit Wicaksana; I Putu Eka Wijaya; Suhaeni Suhaeni; Ali fahmi Syahputra (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2022)
This study aims to determine the factors that affect the quantity of Indonesian fishery commodity exports to eight APEC countries in the period 2002-2021. The eight countries are China, Hong Kong, Japan, USA, Singapore, Malaysia, Thailand and the Philippines. The trade model of this research is formed based on independent variables, namely GDP per capita of Indonesia, GDP per capita of export destination countries, economic distance of each country, export prices, and inflation of the Indonesian. While the dependent variable used is the number of Indonesian fishery commodity exports. In this model, there are four variables that significantly affect the number of Indonesian fishery commodity exports, namely the GDP of the export destination country (X1), the GDP of the exporting country/Indonesia (X2), the economic distance between the two countries (X3) and the export price (X4). While the inflation variable of the exporting country/Indonesia (X5) has no significant effect on the number of exports of Indonesian fishery commodities. The dependent variable can be explained by the independent variables used in the model by 91%, while the remaining 9% is explained by other variables outside the research variables.